PENGARUH PENDAPATAN TERHADAP KONSUMSI PETANI CENGKEH DI KABUPATEN TOLI-TOLI - Hardiyanti Sultan (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
The research aimed to analyze the effect of income on the consumption of clove farmers in Toli-Toli District. The research used a quantitative descriptive analysis. At first, the consumption pattern of the farmers was analyzed and depicted descriptively, then it followed by a simple regression analysis using the SPSS 22 tool to determine the effect of their income on the consumption.   It was found that food consumption was greater than non-food consumption. The expenditure for the food consumption was 65.74% of the total expenditures for consumption. The regression analysis revealed that the income has a positive effect on the consumption. The farmer consumption increases with increasing the farmers’ income. The regression coefficient for consumption was equal to 0.935 which means that each addition of one unit of income will increase the farmers consumption by 0.935 unit, thus the clove farmers can only save their income by 0.07 unit.Keywords : Consumption and Income.